2017
DOI: 10.4172/2472-1654.100049
|View full text |Cite
|
Sign up to set email alerts
|

Principles for Developing an Interprofessional Education Curriculum in a Healthcare Program

Abstract: Interprofessional Education (IPE) has been a pedagogical method which has involved more than one professional discipline. For over the past ten years health professions and disciplines have had a goal to improve the quality of patient care by collaborating with each other [1]. The implementation of IPE has advanced the educational development of students in health sciences and healthcare beyond that of traditional curricula. The result being a greater understanding on the part of each student from different he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 4 publications
1
22
0
6
Order By: Relevance
“…These findings support the call for mandatory interprofessional training in the education of healthcare professionals [ 18 ]. However, there are numerous obstacles to this.…”
Section: Teaching In An Interprofessional and Intercultural Contextsupporting
confidence: 84%
“…These findings support the call for mandatory interprofessional training in the education of healthcare professionals [ 18 ]. However, there are numerous obstacles to this.…”
Section: Teaching In An Interprofessional and Intercultural Contextsupporting
confidence: 84%
“…Por ello, la atención integral de la salud requiere de una educación interprofesional (EIP) como estrategia para conseguirla. Desde el punto de vista conceptual, la EIP parte del supuesto de que la colaboración entre estudiantes de diversas disciplinas produce aprendizajes significativos que se traducirán más tarde en un trabajo colaborativo, en equipo, efectivo, económico y de mayor calidad (10). Además, la EIP propicia sinergias cognitivas y técnicas, facilita la integración de diversas cosmovisiones y el desarrollo de competencias y valores para abogar por el derecho a la salud y propiciar el empoderamiento en salud de las personas, familias y comunidades, por lo que es una estrategia útil para lograr la salud universal y la reducción de inequidades.…”
Section: Educación Interprofesional Para Instrumentarunclassified
“…Having them determine how to engage in IPE, that is, may play the dual role of highlighting the importance of collaborative leadership and team work while also helping them learn essential interprofessional core competencies. Evidence for the value of such control comes from other contexts in which it has been shown that programmes that include the target population in the programme's development show increased chances of the programme's uptake and effectiveness among the target population 9 …”
mentioning
confidence: 99%
“…This focus on building autonomy offers an important step away from focusing simply on the methods used to deliver interprofessional education programmes. Various methods have been shown to either attract or deter students including simulation, case‐based learning and workshops, 5,9 but perhaps it is less the mannequins or human role players that have successfully developed interprofessional health care teams and more that such activities provide an opportunity to take control of one's interprofessional education in a manner that creates motivation to engage 9 . It is important, therefore, that work such as that presented by Ganotice et al continues because whatever the mechanism, we need to continue to find ways to enable students to learn role clarification, team functioning, interprofessional conflict resolution and values/ethics for interprofessional practice.…”
mentioning
confidence: 99%